Participatory budgeting : Is it a useful tool towards co-creation of public services? - Dybał, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The research aim of the present paper was to check whether participatory budgeting fulfills the concept of co-creation of public services in Poland. To achieve this goal, the following research tasks have been implemented: (1) to identify the legal solutions of citizens’ cooperation, (2) to identify the characteristics of participatory budgeting in terms of co-creating public services, (3) to identify the amount and structure of participatory budgeting, (4) to provide cross-country comparison, and (5) to identify difficulties in using participatory budgeting. It has been revealed that in 2021, participatory budgeting was most popular in big cities where it is compulsory. In 2019, Poland (with 2,014 budgets) and Portugal (1,666 budgets) were responsible for 71.69% of all implemented participatory budgets in Europe. In 2018, Europe constituted 48.9% of all worldwide projects, mostly because of their compulsory nature in Poland and Portugal. Participatory budgeting might be successful in its implementation, but needs: involvement of the local community; planning of preparatory activities; communication between all entities involved in the project; appointment of a team that will coordinate the preparation of the participatory budget. According to the research, participatory budgeting is a platform for social activation and providing services better suited to the needs of the inhabitants. Participatory budgeting is a certain form of co-creating public services, as the inhabitants create projects and decide on the allocation of funds for the implementation of public services. Nevertheless, it is a limited version of co-creation, since residents are not involved in all parts of the process. The research covers mainly the years 2018–2022. In the present paper, the following research methods have been used: analysis of scientific literature and normative documents, co-creation methodology, comparative analysis, and statistical analysis.
Keywords: participatory budgeting; co-creation; public services; citizens